Ion source and LEBT of KAHVELab proton beamline - Adhguzel, A.; Aciksoz, S.; caglar, A.; cetinkaya, H.; Esen, S.; Halis, D.; Hamparsunoglu, A.; ilhan, T. B.; Kilicgedik, A.; Kocer, O.; Ogur, S.; Oz, S.; et al. (IOP Publishing Ltd, 2023)
The KAHVE Laboratory, at Bogazici University, Istanbul, Turkey is home to an edu-cational proton linac project. The proton beam will originate from a 20 keV H+ source and will be delivered to a two module Radio Frequency Quadrupole (RFQ) operating at 800 MHz via a low energy beam transport (LEBT) line. Currently, the design phase being over, commissioning and stability tests are ongoing for the proton beamline which is already produced and installed except the RFQ which is being manufactured. This work summarizes the design, production and test phases of the ion source and LEBT line components.
Keywords: Ion sources (positive ions; negative ions; electron cyclotron resonance (ECR); electron beam (EBIS)); Beam Optics; Instruments & Instrumentation